Navigating Educational Crossroads: Unveiling the Cultural Journey of Indonesian Graduate Students in European Scholarship Programs - Dewi Lestari Natalia; Dede Kurniyawan; Dessita Chairani; Liza Erica Panjaitan; Michael Wolter T.W.; Donna Asteria; Nilufar Khodjaeva (Universitas Muhammadiyah Surakarta, 2024)
This research departs from the challenges and adaptation processes undertaken by international students from Indonesia. The research aims to provide a deep understanding of the scholarship alumni in Europe’s academic life during their studies. This research adopts a constructivist paradigm with a qualitative case study approach. The data collection in this research uses purposive sampling techniques with in-depth interviews and the data analysis uses thematic analysis. The subjects are European university alumni from Indonesia who have completed their studies within the past 5 years. There are four themes: study abroad fantasies, a touch of foreign cultures, academic problems and challenges, and academic strategies or solutions. There are also problems and challenges encountered such as academic constraints, stress, and weather. Scholarship alumni in Europe have strategies to adapt, such as traveling while studying, self-management, having a support system, and establishing social interaction with Indonesians. The findings and results can become a foundation document for donors, sponsors, scholarship providers, and the Indonesian Embassy in European countries in creating strategic programs as a provision for students in their studies.